Causes of Failure on Entrepreneurship in Order to Achieve SDG 8 - Ratna L. Nugroho; Hanif Ibrahim (Budapest International Research and Critics University, 2022)
The role of entrepreneurship is very important to achieve SDG 8. The ratio number of entrepreneurs in Indonesia is below 14% of the population. It happens because many people have failed to running a business. The one of reason is such the effect of COVID-19 pandemic. This study aims to find what factors cause failure in entrepreneurship. The factors who associated with failure in entrepreneurship are managerial incompetence, neglect, weak control systems, and insufficient capital. This research method uses a qualitative method with in-depth interviews for data collection. Respondents who were involved in this study were four MSME (Micro Small Medium Enterprise) who have low sale because of the COVID-19 pandemic. Based on the results for the managerial incompetence, entrepreneurs haven’t made business planning, lack business knowledge, marketing management, and others. In the neglect category, entrepreneurs have bad time management and they open new business who not in accordance with their main business or expertise. In the weak control system category, entrepreneurs not control the process of production, inventory, and finance. They don’t separate their organization based on job function. In the insufficient capital category, entrepreneurs struggle to get the loan, and not prepare sufficient capital.